Macroeconomic management on becoming an African oil exporter - Oliver Morrissey; Lars Spreng (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2020)
This paper provides analysis of the macroeconomic management implications of becoming an exporter of oil, taking the case of Ghana and applying to Uganda as a prospective exporter. The paper proceeds in two steps. First, we construct a Dynamic Stochastic General Equilibrium (DSGE) model of a primary commodity exporting developing country calibrated to Ghana and Uganda and simulate the impulse response to shocks to the oil price and oil production. Second, using parameters from the DSGE model to obtain priors for parameter values, we use a Structural Vector Autoregressive (SVAR) with monthly data over 2001 to 2019 to estimate the response to oil shocks as an importer for both countries and as an exporter for Ghana after 2010. The DSGE results suggest that although an oil price shock generates appreciation and initially output falls, there are reductions in interest rates and inflation and ultimately output increases. The larger the oil sector the greater the appreciation and inflationary effects, but output rises more quickly and there are larger increases in wages and taxes. The SVAR results for Ghana when exporting suggest an initial depreciation in response to an oil price shock, with a reduction in inflation, but the immediate negative output response slowly turns positive (and becomes consistent with the DSGE). When Ghana and Uganda are importers, oil price shocks generate appreciation, mild inflation and interest rate reductions, so although output declines initially it rises after a year and this persists. The analysis suggests that the adoption of inflation targeting, in conjunction with an improved monitoring of macroeconomic developments, has mitigated the effects of oil price shocks on domestic variables in Ghana and Uganda.
Keywords: F31; F35; O11; O55; 330; Oil; Exchange Rates; DSGE; SVAR; sub-Saharan Africa (Ghana; Uganda)